Building and Sustaining Community Cyber‐Infrastructure for the Hydrologic Sciences. (19th November 2013) - Arrigo, Jennifer; Tarboton, David; Couch, Alva
<x xml:space="preserve">Abstract</x> As part of its mission to empower scientists to discover, use, store, and share water data from multiple sources, the Consortium of Universities for the Advancement of Hydrologic Sciences, Inc. (CUAHSI) Water Data Center (http://wdc.cuahsi.org) held a conference to provide a forum for researchers working in hydroinformatics and modeling, scientists using and managing large amounts of data, and others interested in advancing standards and best practices for water data access, discovery, and sharing.